A Reversible Rocksalt to Amorphous Phase Transition Involving Anion Redox. Issue 1 (December 2018) - Sakuda, Atsushi; Ohara, Koji; Kawaguchi, Tomoya; Fukuda, Katsutoshi; Nakanishi, Koji; Arai, Hajime; Uchimoto, Yoshiharu; Ohta, Toshiaki; Matsubara, Eiichiro; Ogumi, Zempachi; Kuratani, Kentaro; Kobayashi, Hironori; et al.
Abstract The charge-discharge capacity of lithium secondary batteries is dependent on how many lithium ions can be reversibly extracted from (charge) and inserted into (discharge) the electrode active materials. In contrast, large structural changes during charging/discharging are unavoidable for electrode materials with large capacities, and thus there is great demand for developing materials with reversible structures. Herein, we demonstrate a reversible rocksalt to amorphous phase transition involving anion redox in a Li2 TiS3 electrode active material with NaCl-type structure. We revealed that the lithium extraction during charging involves a change in site of the sulfur atom and the formation of S−S disulfide bonds, leading to a decrease in the crystallinity. Our results show great promise for the development of long-life lithium insertion/extraction materials, because the structural change clarified here is somewhat similar to that of optical phase-change materials used in DVD-RW discs, which exhibit excellent reversibility of the transition between crystalline and amorphous phase.